Applying Mind Map in Teaching History in Primary Schools - Case Study of Dak Lak Province, Vietnam - Le, Thi Thuy An; Nguyen, Thi Anh Mai; Bui, Thi Tam; Luu, Thi Diu; Dinh, Thi Kieu Loan (Universitas Negeri Semarang, 2021)
This article discusses the role and meaning of the application mind map in teaching history in primary schools in Vietnam. In doing so, this paper studies requirements, designing process and then proposes satisfactory methods to apply mind map in teaching history suitably in Vietnamese education environment. By doing so, the research partly improves the quality and effectiveness of historical lessons in primary schools (class 4 and 5) in to obtain a higher aim of developing students abilities. In this paper, the author applies mixed researching methods including analyzing data, pedagogical viewing, surveying, and pedagogical experiment and then evaluating educational experience. The researchs results support previous studies about the role and effectiveness of using mind map in teaching in general and in teaching history in particular. The author also suggests that in to promote the success of mind map in education, teachers need to mix several teaching methods and technics.